2018
DOI: 10.1073/pnas.1806268115
|View full text |Cite
|
Sign up to set email alerts
|

Functional and evolutionary characterization of a secondary metabolite gene cluster in budding yeasts

Abstract: Secondary metabolites are key in how organisms from all domains of life interact with their environment and each other. The iron-binding molecule pulcherrimin was described a century ago, but the genes responsible for its production in budding yeasts have remained uncharacterized. Here, we used phylogenomic footprinting on 90 genomes across the budding yeast subphylum Saccharomycotina to identify the gene cluster associated with pulcherrimin production. Using targeted gene replacements in Kluyveromyces lactis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
105
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 60 publications
(67 reference statements)
7
105
0
3
Order By: Relevance
“…The patchy distribution of the genes both within a single species and between closely related bacteria suggests loss of the genes overtime, rather than reoccurring acquisition. This pattern of gene loss and distribution is consistent with the profile observed in yeast (46). However, given the knowledge that at least two routes have evolved for pulcherriminic acid production (46,47), we cannot exclude the possibility that other species also synthesize pulcherriminic acid using an as yet unidentified pathway.…”
Section: Sequestration Of Iron In Biofilmssupporting
confidence: 80%
See 3 more Smart Citations
“…The patchy distribution of the genes both within a single species and between closely related bacteria suggests loss of the genes overtime, rather than reoccurring acquisition. This pattern of gene loss and distribution is consistent with the profile observed in yeast (46). However, given the knowledge that at least two routes have evolved for pulcherriminic acid production (46,47), we cannot exclude the possibility that other species also synthesize pulcherriminic acid using an as yet unidentified pathway.…”
Section: Sequestration Of Iron In Biofilmssupporting
confidence: 80%
“…Pulcherrimin has been observed to be made by both eukaryotic and prokaryotic microorganisms (27,45). It is, however, only more latterly that the biosynthetic pathways involved have been elucidated (46,47). Our comparative genomic analysis revealed that the genes needed for pulcherriminic acid synthesis and secretion (yvmC, cypX and yvmA) were found in the genome or on plasmids of species beyond B. subtilis.…”
Section: Sequestration Of Iron In Biofilmsmentioning
confidence: 86%
See 2 more Smart Citations
“…Pulcherriminic acid is formed by the oxidation of cyclodileucine (cyclo(Leu-Leu) (24,25). Pulcherrimin was first described in yeasts more than 60 years ago, but only very recently the four genes involved in its biosynthesis and transport in Kluyveromyces lactis have been identified (26), and the structure of the molecule synthesized by yeasts has not been determined by modern analytical methods. However, pulcherrimin is also produced by certain bacteria such as Bacillus licheniformis, where the two genes yvmC and cypX, coding for a cyclodipeptide synthase and cytochrome P450 oxidase, respectively, are responsible for its biosynthesis (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%